2020
DOI: 10.2341/19-153-l
|View full text |Cite
|
Sign up to set email alerts
|

Is Conventional Resin Cement Adhesive Performance to Dentin Better Than Self-adhesive? A Systematic Review and Meta-Analysis of Laboratory Studies

Abstract: Clinical Relevance Conventional multistep resin cements presented higher adhesive performance to dentin than simplified self-adhesive cements, which is an important criterion for indirect restoration prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
0
38
0
5
Order By: Relevance
“…The bonding mechanism of adhesive systems to root dentin has a micromechanical nature, and is based on three parameters: (I) penetration of bonding agent into the demineralized dentin (formation of hybrid layer), (II) formation of resin tags, and (III) formation of lateral adhesive branches. (6,31) Irrespective of presence of a significant difference, the results of these two studies indicated that the bond strength decreased from the coronal towards the apical region in all groups. One reason can be the decreased density and diameter of dentinal tubules from the coronal towards the apical region.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The bonding mechanism of adhesive systems to root dentin has a micromechanical nature, and is based on three parameters: (I) penetration of bonding agent into the demineralized dentin (formation of hybrid layer), (II) formation of resin tags, and (III) formation of lateral adhesive branches. (6,31) Irrespective of presence of a significant difference, the results of these two studies indicated that the bond strength decreased from the coronal towards the apical region in all groups. One reason can be the decreased density and diameter of dentinal tubules from the coronal towards the apical region.…”
Section: Discussionmentioning
confidence: 90%
“…In other words, dentin-resin cement interface is a weak interface in terms of bond strength. (5,6) Universal adhesives are capable of bonding to different substrates and can be used in selfetch and total-etch modes. (7,8) Considering the relatively recent introduction of universal adhesives to the dental market, information regarding their properties is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…SA Luting Multi has a new composition that contained a silane coupling agent in the paste, so the manufacturer was does not recommend the use of any silane primer before cementation with this material. In this experiment, it was hypothesized that the direct application of a silane primer would provide a higher bond strength than using the newly developed self-adhesive resin cement containing a silane coupling agent; previous studies have recommended multi-step procedures improve the performance of adhesives [25,26]. However, the results of the µTBS showed no difference in the bond strength of the two types of resin cement.…”
Section: Discussionmentioning
confidence: 97%
“…The acidic groups interact with the calcium and phosphate of the hydroxyapatite, with setting reactions involving a complex dynamic mechanism [ 11 ]. The main setting reaction occurs via free-radical polymerization, initiated either by curing light or by a redox system, allowing the setting polymerization reaction in this acidic environment [ 18 ]. This dynamic setting mechanism, related to the activation mode of the polymerization reaction (chemical or dual) and to the importance of the pH-neutralization, could possibly affect the physicochemical properties of the self-adhesive cements [ 19 ].…”
Section: Discussionmentioning
confidence: 99%